2018
DOI: 10.18203/2319-2003.ijbcp20181647
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of haemovigilance amongst healthcare professionals in Nashik, Maharashtra, India

Abstract: Background: Haemovigilance Programme of India was launched in 2012 with the purpose to identify, analyse and learn the complications related to transfusion and blood donation, in order to avoid such complications in future. Though it is essential to identify the Adverse Transfusion Reactions (ATR) to reduce the incidence and make transfusion easier; there are rare reports available about knowledge, attitude, and practice (KAP) of Healthcare Professionals (HCP) for haemovigilance.Methods: In this cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…According to the study carried out in Burkina Faso in 2017, 51.5% have witnessed a blood transfusion accident [26]. In India, a study carried out in 2018 indicated that 38.6% of staff have witnessed it [50]. This remains close to our study, where 44% have already witnessed a blood transfusion accident due to incompatibility.…”
Section: Discussionsupporting
confidence: 81%
“…According to the study carried out in Burkina Faso in 2017, 51.5% have witnessed a blood transfusion accident [26]. In India, a study carried out in 2018 indicated that 38.6% of staff have witnessed it [50]. This remains close to our study, where 44% have already witnessed a blood transfusion accident due to incompatibility.…”
Section: Discussionsupporting
confidence: 81%
“…The results are similar to various studies conducted on Knowledge, attitude and practices regarding hemovigilance. 10 Only 48% of the practitioners thought that transfusion reactions should be reported, 70% of the practitioners thought that transfusion reactions can be dangerous. 40% of practitioners told that seminars/CMEs should be planned.…”
Section: Discussionmentioning
confidence: 99%
“…As the way to improve Haemovigilance reporting, maximum felt that more training should be conducted, reporting forms to be made easier, Toll-free helpline reporting to be made mandatory, organizing CME/workshops and availability of the mobile application [6]. Seminars/CMEs/Workshops can be useful in spreading knowledge regarding Haemovigilance to various doctors and other health care professionals which can help in creating awareness [18].…”
Section: Most Of the Pgs Knew Transfusion Reactions Analogous To Othe...mentioning
confidence: 99%